FDI screening regulation and the recent EU guidance: What options do member states have? - Jens Velten (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The EU seeks to establish a harmonized FDI screening landscape, but leaves the ultimate decision to member states. Besides screening mechanisms on the grounds of "security or public security" pursuant to the FDI screening regulation, member states have other options, namely a narrower Fundamental Freedom Option.
Keywords: 330